Structural Study of Chemical, Optical, and Biological Sensors - poladian, qumars (Journal of Natural Sciences – Kabul University, 2024)
Chemical sensing (chemical sensors) is a part of the information acquisition process in which a precise understanding of the chemical composition of a system is obtained in real-time. In this process, an amplified electronic signal results from the interaction between some chemical species and the sensor. In general, interaction in sensors includes two stages: identification and amplification. The common example of measuring the pH of different environments with a glass electrode, determination of concentration, pressure, and temperature, detection of different gases, and other cases can be presented. In this review article, an attempt is made to provide information about various sensors, including chemical sensors and other types of sensors, and to reveal their respective advantages over each other.